Phase equilibria of (CO2 + butylbenzene) and (CO2 + butylcyclohexane) at temperatures between (323.15 and 423.15) K and at pressures up to 21 MPa - Hou,S-X; Maitland,GC; Trusler,JPM (Fluid Phase Equilibria, 2014)
Experimental measurements of the phase equilibria of (CO2 + butylbenzene) and (CO2 + butylcyclohexane) have been made with an analytical apparatus at temperatures of (323.15, 373.15 and 423.15) K at pressures from 2 MPa to the mixture critical pressure. These are the first results to be published for (CO2 + butylcyclohexane), while for (CO2 + butylbenzene) they are the first at pressures above 6 MPa. To model the data, we use the Peng–Robinson equation of state with Wong–Sandler mixing rules incorporating the NRTL equation. The model describes the measured bubble point curves very well at all temperatures, except close to the mixture critical points at high pressures. The dew point curves are described well only at the lowest temperature; otherwise, deviations increase in the approach to the mixture critical point.